Letter from Campbell Morfit to James Curtis Booth, March 17, 1851 - Morfit, Campbell (1851)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth regarding a job he is doing. Morfit writes, “No one shall, in my profession, degrade me to a mere mechanic. I must be paid for my art as well as my time.”
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists